Living the French Revolution and the Age of Napoleon - Desan, Suzanne, 1957-; Teaching Company (Chantilly, Va. : Teaching Company, 2013)
A lecture series on the French Revolution. The 25 years between the onset of the French Revolution in 1789 and the Bourbon Restoration after Napoleon in 1814 is an astonishing period in world history. This era shook the foundations of the old world and marked a permanent shift for politics, religion, and society ; not just for France, but for all of Europe.
Volume 4. Disc 19. Disc 20. Disc 21. Disc 22. Disc 23. Disc 24. Building power: general and first consul ; Napoleon becomes Emperor-- Napoleon's ambitions in the new world ; Taking on the great powers-- Expanding the empire ; France during the empire -- Living under the empire ; The Russian campaign-- Napoleon's fall and the Hundred Days ; Waterloo and beyond-- Emerging political models ; Revolutionary legacies.
Lecture notes and program information contained in course guidebook.
Includes bibliographical references (p. 359-373) in course guidebook.
Lecturer: Professor Suzanne M. Desan, University of Wisconsin-Madison.
Keywords: Napoleon -- I, -- Emperor of the French, -- 1769-1821.; France -- History -- Consulate and First Empire, 1799-1815.